S53P4 Bioactive Glass Granules for the Management of Bone, Joint, and Related Soft-Tissue Infections: An Updated Review - Chayanin Angthong; Tyler Vichayabhai; Phurin Tatiya-apitham (Ortopedia Traumatologia Rehabilitacja, 2025)
BACKGROUND: Bioactive glass S53P4 has drawn increasing interest for its use in managing chronic osteomyelitis, infected non-unions, and related soft-tissue infections. This review synthesizes clinical evidence with emphasis on comparative studies versus autologous bone grafts, allografts, and antibiotic carriers. MATERIAL AND METHODS: We performed a comprehensive search of PubMed, EMBASE, and Scopus (January 2013 to September 2025) that identified human clinical studies reporting outcomes of S53P4 in bone, joint, and related soft-tissue infections. Search terms combined 'S53P4' OR 'bioactive glass' with 'osteomyelitis', 'bone infection', 'infected non-union', 'joint infection', and 'dead space management'. The data were screened, reviewed, extracted, and analyzed in accordance with the PRISMA guideline. RESULTS: Across heterogeneous cohorts, infection eradication rates typically range from 80-95% with S53P4, bone healing is comparable to autograft, and complication rates are low. Comparative data suggest non-inferior infection control and bone consolidation relative to autograft/antibiotic-polymethylmethacrylate, with potential advantages for one-stage care and reduced length of stay. CONCLUSION: S53P4 bioactive glass provides infection control and bone regeneration outcomes comparable to autograft and selected antibiotic carriers in chronic osteomyelitis and infected non-unions. Its antimicrobial and osteoconductive properties enable effective one-stage treatment in many cases, with a favorable safety profile and potential cost savings. High-quality randomized trials remain limited, but current evidence supports S53P4 as a viable, cost-effective adjunct in orthopedic infection surgery.
Keywords: Orthopedic Infections and Treatments; Bone Tissue Engineering Materials; Bone fractures and treatments